2021
DOI: 10.1002/ep.13732
|View full text |Cite
|
Sign up to set email alerts
|

A phosphogypsum‐based road material with enhanced mechanical properties for sustainable environmental remediation

Abstract: An integrated approach for sustainable use of phosphogypsum (PG) byproducts as road materials was developed. For the purpose of this study, several formulations of PG-based material have been performed to evaluate its potential application for road base layers. Physico-chemical properties, mechanical strengths and environmental

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A mixture of 46.5% sand, 46.5% PG, and 7% cement was prepared, and its mechanical strength and leaching behavior were discussed [121]. The obtained results indicated that the early and final compressive strengths of the stabilized material were higher than those of conventional road subgrade materials, reaching 2200 and 3500 kPa at 28 and 360 days, respectively.…”
Section: Road Bases and Pavement Materialsmentioning
confidence: 99%
“…A mixture of 46.5% sand, 46.5% PG, and 7% cement was prepared, and its mechanical strength and leaching behavior were discussed [121]. The obtained results indicated that the early and final compressive strengths of the stabilized material were higher than those of conventional road subgrade materials, reaching 2200 and 3500 kPa at 28 and 360 days, respectively.…”
Section: Road Bases and Pavement Materialsmentioning
confidence: 99%
“…Phosphogypsum is an industrial solid waste generated during the production of wet process phosphoric acid, the main component is CaSO4• 2H2O, in addition to a variety of other impurities, such as phosphorus, fluorine, eutectic phosphorus, phosphate and organic matter [26] , resulting in large fluctuations in the quality of phosphogypsum, which is very unfavorable to its resource utilization. At present, the development and application of phosphogypsum building materials in Yunnan, Guizhou, Hubei and Chongqing provinces and cities in China have taken shape, with the main products being modified moisture-proof lightweight gypsum wallboard, gypsum putty powder, gypsum mold box for hollow building cover structure and gypsum roadbed bedding, etc [27] . Huancheng Song [28] prepared sintered bricks from phosphogypsum in Hubei, Guizhou, and Yunnan, and the results showed that phosphogypsum has certain self-sintering properties, and the sintering properties of phosphogypsum were substantially improved by adding 2% of sintering additives, and the compressive strength was up to 39.97±3.03 MPa, which was in accordance with the national standard for load-bearing wall bricks.…”
Section: Research Status Of Phosphogypsum-based Wall Materialsmentioning
confidence: 99%
“…Stabilised and cured PG can be used to replace traditional road materials, thus reducing rock and soil mining and protecting the environment while increasing PG utilisation for sustainable development. A mixture of 46.5% sand, 46.5% PG, and 7% cement was prepared, and its mechanical strength was discussed ( Zmemla et al., 2022 ). The prepared mixture was subjected to conventional compressive and tensile strength tests as well as Young’s modulus test, the results of which indicated that the early and final compressive strengths of the stabilised material were higher than those of conventional road subgrade materials, reaching 2200 and 3500 kPa at 28 and 360 days, respectively.…”
Section: Application Of Pg In Road Engineeringmentioning
confidence: 99%